Pengaruh Kepercayaan, Kualitas Layanan, Lokasi Dan Pengaruhnya Terhadap Kepuasan Anggota BMT Assafiyah Kota Gajah Lampung Tengah - Ratmono; Slamet Tedy Siswoyo; Muchlas Alfandi (Jurnal Manajemen DIVERSIFIKASI, 2024)
Increasing banking competition is marked by the emergence of many financial institutions.This competition can be seen from the variety of products or services offered, one of which isBMT Assyafiiyah. banking companies or BMT Assyafiiyah must implement a good strategy sothat members are interested in saving at financial institutions. to attract member satisfactionis done by implementing the right strategy, including Trust, Quality of Service, and Location.The data analysis method used is quantitative and qualitative analysis. and the population inthis study were members of BMT Assyafiiyah, totaling 1,027 members with a sample of 91members and tested using: validity test, reliability test, normality test, linearity test,homogeneity test, multiple linear regression analysis, T-test, F test, Test the coefficient ofdetermination R2 and statistical hypothesis. Based on the results of the study, shows that theindicators used in the framework variables including Trust, Service Quality, and Locationhave a positive and significant influence on satisfaction. This shows that if BMT Assyafi'iyahKota Gajah can provide good satisfaction, it will facilitate BMT Assyafi'iyah Kota Gajah inrecruiting members. Conclusions in this study are: There is a positive and significant effect ofTrust, Service Quality, and Location on Member Satisfaction at BMT Assyafi'iyah theNational Blessing of the Kota Gajah.